2019
DOI: 10.1111/dme.14101
|View full text |Cite
|
Sign up to set email alerts
|

Use of capillary glucose combined with other non‐laboratory examinations to screen for diabetes and prediabetes

Abstract: Aim To evaluate the value and feasibility of capillary glucose assessment, combined with other non‐laboratory measures, in screening for diabetes and prediabetes in the community. Methods In this cross‐sectional study, we assessed fasting capillary glucose, fasting plasma glucose, and both capillary glucose and plasma glucose values after 2‐h oral glucose tolerance tests in a total of 3736 samples. We determined the optimal threshold of capillary glucose using receiver‐operating characteristic curve analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Various studies done previously showed strong positive correlation between capillary glucose and venous plasma glucose 5 . Hence capillary glucose measurement can be used as alternative to venous glucose in resource limited situations for screening of diabetes mellitus 5 .…”
Section: Methodsmentioning
confidence: 82%
“…Various studies done previously showed strong positive correlation between capillary glucose and venous plasma glucose 5 . Hence capillary glucose measurement can be used as alternative to venous glucose in resource limited situations for screening of diabetes mellitus 5 .…”
Section: Methodsmentioning
confidence: 82%
“…The comparability between the cOGTT and vOGTT alludes to the former in identifying people with prediabetes or T2DM. [28][29][30][31][32] The higher mean capillary glucose values, compared with venous glucose values, potentially identify more people with suspected dysglycemia, while those with normal capillary glucose results are least likely to have wrong diagnosis of prediabetes or T2DM. The results suggest a possible two-tiered approach: those with abnormal capillary OGTT will proceed to the conventional OGTT for definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, multiple blood collections may increase people's pain and decrease their compliance. In general, fasting plasma glucose (FPG) is more commonly used in diabetes screening, so randomised blood collection is not allowed, whereas most people suffering from diabetes in China present with isolated postprandial hyperglycaemia 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…In general, fasting plasma glucose (FPG) is more commonly used in diabetes screening, so randomised blood collection is not allowed, whereas most people suffering from diabetes in China present with isolated postprandial hyperglycaemia. 4,5 Therefore, effective diagnosis is impossible for the majority of individuals who visit the clinic after eating, those who cannot manage long-term fasting or repeated blood drawing, and those with poor compliance. Consequently, there is a greater need for a sensitive, simple and effective method to detect diabetes randomly.…”
Section: Introductionmentioning
confidence: 99%